To evaluate LinkedIn as a social network used to build personal brand among young professionals - Komani, Siphosethu (The IIE, 2019)
Personal branding connotes a way in which individuals can stand out from the crowd through applying a series of self-promotion methods which emphasise on their unique selling points. LinkedIn is a social networking site widely known as a recruitment platform that offers its users the opportunity to create professional online profiles accessible to industry stakeholders. Although previous literature on personal branding and social media exists, they often highlight personal brand as a means to achieve fame and popularity and fail to address whether applying personal brand building principles and techniques can have practical implications in professional career fields. This research study aims to evaluate LinkedIn as a personal brand building platform through a content analysis of several user profiles, corroborated by in-depth interviews. The researcher seeks to explore how each of the sampled profiles makes use of LinkedIn’s features to build their brand.
Keywords: Brand; Personal branding; Social networking; Social media; Content analysis